Corrosion Inhibition of Mild Steel in Hydrochloric Acid by Sodium Lauryl Sulfate (SLS). Issue 2 (2008) - Kumar, Atul
Abstract : Effect of Sodium Lauryl Sulfate (SLS), a surfactant on corrosion of mild steel in 1 M hydrochloric acid was studied using three techniques namely: weight loss, electrochemical polarization and metallurgical research microscopy. Results obtained reveal that SLS is good inhibitor and shows very good corrosion inhibition efficiency (IE). The IE was found to vary with concentration of inhibitor and temperature. The electrochemical polarization result revealed that SLS is anodic in nature.